PENGARUH CELEBRITY ENDORSER TERHADAP PURCHASE INTENTION MELALUI BRAND CREDIBILITY - Said Luthfi Alatas; Mirza Tabrani (Jurnal Manajemen Inovasi, 2018)
This study aims to determine the effect of celebrity endorser on purchase intentions with variables brand crediility as mediators. The sample used in this study is 125 respondents who are people have watched Yamaha Nmax ads in Banda Aceh. Purposive Sampling is used as a sampling technique. Partial Least Square analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that Celebrity Endorser effect on Purchase Intention. Celebrity Endorser affects brand credibility. In addition, the results obtained that the brand credibility variable acts as a full mediation on the celebrity endorser variable to purchase Intention. And brand credibilty effect on purcahase intention. The higher the effect of perceived celebrity endorser, the higher the brand credibility of Yamaha Nmax product, the stronger the purchase intention is owned by the consumer. Keyword: Celebrity Endorser, Brand Credibility, Purchase Intention, Yamaha Nmax.